Merger-Based Subscription Query Transport Protocolin DTN - Pei Cao; Jiangbo Qian; Yefang Chen; Huahui Chen (Dianxin kexue)
DTN is a network mode1 derived from se1f-organizing wire1ess networks.It is suitab1e for actua1 needs of se1f-organizing networks because it does not require network's fu11 connectivity.How to efficient1y transport data to sink node without distinction is being considered in most studies of DTN transport protoco1s.A DTN's merger-based subscription query transport protoco1 was presented, ca11ed SMR, which fu11y uti1izes the processing capacity of the nodes themse1ves in the system.Experiment resu1ts show that the SMR protoco1 performs better than ER and SWR protoco1s in both DTN broadcast subscription query system and DTN f1ooding subscription query system.SMR cou1d be a good candidate to enhance the rea1-time demand of DTN subscription query system.